Effectiveness Of Celebrity Endorsement on Advertisement in Achieving Consumer Brand Preference - Adedeji , Amos Ojo (Future Science / FSH-PH Publications, 2021)
The instrument of celebrity endorsement has become a pervasive element in advertising. This paper qualitatively examining the effectiveness of celebrity endorsement on advertisement in achieving consumer brand preference. The study revealed some impacts of acquiring celebrity for endorsement such as building awareness, quick connect, means of brand differentiation and better brand image among others. The study identified some challenges associated with celebrity endorsement which are not limited to celebrity overshadows the brand, conflicting image and influence of celebrity moral violation on brands. The paper concludes by recommending careful choosing of celebrity that his/her value will have close link with the brand been endorsed and improvement on the quality of the product by the producer as possible measures to avert the challenges of using celebrity in advertising. Using celebrities that have moral and are well placed in the society for advertisement is also key.